2016
DOI: 10.1016/j.jpowsour.2016.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reversible and irreversible degradation rates of polymer electrolyte membrane fuel cells tested in automotive conditions

Abstract: • Discrimination between reversible and irreversible degradation • Determination of voltage loss rates at different loads in a single durability test • Quantitative evaluation of reversible voltage decay by linear-exponential function • Recovery of reversible voltage losses by shutdown recovery procedure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 30 publications
0
49
0
Order By: Relevance
“…The degradation studies have been usually performed using either accelerated stress tests (AST) or in constant operation conditions. Automotive operation conditions, however, exhibit a highly dynamic load profile with shut‐down interruptions that have a significant impact on the recovery of reversible losses . To the best of our knowledge, a systematic study on the impact of Pt‐loading on both performance and degradation performed in automotive operation conditions has not been published so far.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…The degradation studies have been usually performed using either accelerated stress tests (AST) or in constant operation conditions. Automotive operation conditions, however, exhibit a highly dynamic load profile with shut‐down interruptions that have a significant impact on the recovery of reversible losses . To the best of our knowledge, a systematic study on the impact of Pt‐loading on both performance and degradation performed in automotive operation conditions has not been published so far.…”
Section: Introductionmentioning
confidence: 62%
“…It can be concluded that cathode Pt loadings between 0.3 and 0.4 mg cm −2 represent an upper threshold value below which reversible degradation effects have a major impact on the performance decay independent on the current density at which the cells are operated. A similar behavior has been observed in our recent paper where reversible and irreversible degradation of MEAs with cathodic loadings of 0.4 and 0.2 mg cm −2 has been studied .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quick failure of cell‐1 tested at 64 °C was possibly due to this test station shut down. The recovery of OCV after each shut down and restart was observed , and could be explained by water accumulation in the stack that increases the hydration level of the MEA. The OCV lifetime for the stack at 95 °C was determined to be 168 h, while the lifetime of the stack at 64 °C was remarkably extended beyond 700 h. Since the testing was stopped after 700 h of OCV testing, the OCV lifetime of the samples was extrapolated with linear fitting of the experimental OCV curve from 300 h to 700 h. The lifetime of the sample tested at 64 °C/60% RH was estimated as 1,100 h, demonstrating over one order of magnitude longer lifetime than the baseline (82 h at 95°C/30% RH, see Table ).…”
Section: Resultsmentioning
confidence: 94%
“…However, operating with large and fast transients in a load power is likely to drastically reduce the service life of the fuel cell, mainly due to failure, by various mechanisms, of the cells' membrane-electrode assemblies [14][15][16]. Fuel cell hybrid propulsion systems allow, by adopting appropriate energy management strategies [17][18][19][20][21], the use of the fuel cell as a stationary power generator.…”
Section: Structure and Operating Principles Of An Electric Vehicle Pomentioning
confidence: 99%